Efektivitas Aplikasi TUKKOT ASI Dalam Peningkatan Breastfeeding Self-Efficacy dan Sikap Ibu Hamil Dalam Kesiapan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Gunung Tinggi - Anna Waris Nainggolan; Imarina Tarigan; Siti Nurmawan Sinaga; Humaida Hanim; Imran Surbakti; Edy Marjuang Purba (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Exclusive breastfeeding is the most effective public health intervention for reducing infant morbidity, mortality, and the risk of stunting; however, global and national coverage rates remain below established targets, partly due to low breastfeeding self-efficacy and suboptimal maternal attitudes during the antenatal period. This study aimed to analyze the effectiveness of the TUKKOT ASI Application, which is based on the Batak local wisdom of “Mambosuri,” in improving breastfeeding self-efficacy and pregnant women’s attitudes toward readiness for exclusive breastfeeding. A quasi-experimental design with a pretest–posttest control group approach was employed involving 40 third-trimester pregnant women in the working area of Gunung Tinggi Public Health Center in 2025, selected through purposive sampling. The instruments used were the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF) and a validated attitude questionnaire based on the Theory of Planned Behavior. Data were analyzed using the Wilcoxon test and chi-square test at a significance level of p<0.05. The results showed a significant increase in breastfeeding self-efficacy (mean 10.1±3.7 to 16.8±2.2; p=0.001) and attitudes (mean 5.7±1.4 to 7.9±1.5; p=0.003) following the intervention. Significant associations were found between self-efficacy (p=0.028) and attitudes (p=0.001) with readiness for exclusive breastfeeding. Mothers with higher self-efficacy and positive attitudes were more likely to demonstrate better readiness. It is concluded that the TUKKOT ASI Application is an effective culturally based digital intervention model to enhance pregnant women’s readiness for exclusive breastfeeding and has the potential to be integrated into primary healthcare services.